AN ANALYSIS OF THE QUALITY OF TEACHER – MADE MULTIPLE CHOICE TESTS USED AS SUMMATIVE ASSESSMENT FOR ENGLISH SUBJECT AT SMP NEGERI 5 SINGARAJA - Tikvi Yulia Wahyu Saputri (Jurnal IKA, 2020)
The teacher – made multiple choice test that used by the teachers to assess the students’ level must have a good quality by following certain norms in constructing it. This study was conducted to analyze the quality of the teacher – made multiple choice tests used as a summative assessment especially for middle test in the first semester at SMP Negeri 5 Singaraja. This study used content analysis design. The datawere obtained from 4 different teacher – made multiple choice tests with the total 100 items. Document analysis was used to compare the teacher – made multiple choice tests with the norms in making a good multiple choice test to decide the quality of each item. Then, the interview was done to get additional information. The result shows that all of the items of teacher – made multiple choice tests fulfilled more than 75% norms, means that they belong to very good quality. However the students’ National Examination score was low.Thus, it can be concluded that the quality of teacher – made MCT is not the only factor that affects the students’ National Examination score.